Testing Blood Glucose May be Useful in the Management of Dengue - Hasanat, MA; Ananna, MA; Ahmed, MU; Alam, MN (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):382-5 The abstract of this article is available on the PubMed website